Blast Vibration Analysis. - Bollinger, G. A. (Dover Publications, 2018)
This volume focuses on the origin, transmission, and types of elastic waves in solid media, covering the physical laws involved in wave analysis and the mathematical methods for analyzing wave phenomena. 1971 edition.
Keywords: Blast effect.; Vibration.; Seismic waves.; Seismometry.; elektronické knihy; electronic books